Gender-related differences in the use and perception of verbal insults: the Bosnian perspective - Špago, Džemal (Lingua Posnaniensis, 2020)
The paper explores potential gender-linked differences in the use and perception of insulting language among Bosnian university students. The respondents were asked to provide one-word answers to four questions about the worst male-directed and female-directed insults, and about one-word descriptions of a male and female person who they view as the most detestable. The results indicate that the male and female respondents have a similar perception of the worst male-directed (lack of masculinity) and, to a lesser extent, femaledirected insults (sexual looseness). Surprisingly, insults of homosexual nature, as well as those pertaining to being unethical and physically unattractive were rarely mentioned. The results also reveal significant gender -of-insulter differences in the use of offensive words in reference to the most disliked person, as well as the tendency by the respondents of both genders to avoid using those insults that they perceive as the harshest.